Improving web-based problem solving skills of students with a novel game-based Intelligent Tutoring System - Hooshyar D.; Ahmad R.B.; Yousefi M.; Fathi M.; Horng S.-J.; Hooshyar M.; Dooraki A.R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Artificial intelligence; Bayesian networks; Big data; Computer aided instruction; Computer games; Computer programming; Computer systems programming; Decision making; Education computing; Intelligent vehicle highway systems; Students; Teaching; Websites; Computer Assisted Instruction; Game-Based; Game-based Learning; Intelligent tutoring system; Introductory programming; Learning environments; Novice programmer; Web-based problem solving; Problem solving